Efficient and durable multifunctional nickel-doped cobalt phosphate hydrate electrocatalysts for hybrid supercapacitors and zinc–air batteries - Ankinapalli, Obula Reddy; Krishna, B. N. Vamsi; Lee, Young Jun; Natarajan, Logeshwaran; Ayyaluri, Ramakrishna Reddy; Yu, Jae Su (Royal Society of Chemistry, 2026)
High-performance and long-life cycle supercapacitor (SC) electrodes and air cathodes are essential for the development of efficient hybrid SCs (HSCs) and rechargeable zinc–air batteries (ZABs). In this report, we developed a novel nickel (Ni)-doped cobalt phosphate hydrate ((Ni/Co)3(PO4)2·8H2O) material via a single-step hydrothermal process, which was employed in SC electrodes and bifunctional electrocatalysts. The doping of Ni metal into the material effectively enhanced its SC performance and electrocatalytic properties. The (Ni/Co)3(PO4)2·8H2O SC electrode exhibited an excellent specific capacity/capacitance of 220/1760 (mAh g−1/F g−1) with a superior rate capability of 74.5%. More importantly, the (Ni/Co)3(PO4)2·8H2O SC electrode exhibited an outstanding capacity retention of 92% after 100 000 cycles. The assembled (Ni/Co)3(PO4)2·8H2O//activated carbon HSC device exhibited high energy and power densities of 47.28 Wh kg−1 and 5588.48 W kg−1, respectively. Moreover, the prepared HSC exhibited an excellent capacitance retention of 95% after the completion of 100 000 cycles. The oxygen evolution reaction overpotential of (Ni/Co)3(PO4)2·8H2O was 310 mV, which is lower than those of Co3(PO4)2·8H2O (350 mV), RuO2 (340 mV), and IrO2 (330 mV) in 1 M KOH. (Ni/Co)3(PO4)2·8H2O showed decent onset (Eonset) and half-wave (E1/2) potentials of 0.86 and 0.756 V, respectively. Specifically, the (Ni/Co)3(PO4)2·8H2O-based ZAB exhibited excellent open circuit voltage (1.425 V), specific capacity (733 mAh (gZn)−1), and power density (160.385 mW cm−2) values compared to those of the Pt–C + RuO2-based ZAB. The (Ni/Co)3(PO4)2·8H2O-based ZAB exhibited superior cycling stability of 70 h at 2 mA cm−2. Following the above advantages, the SC and ZAB performances of the (Ni/Co)3(PO4)2·8H2O material create a novel path for efficient energy storage applications.